2000
DOI: 10.1364/ol.25.000375
|View full text |Cite
|
Sign up to set email alerts
|

Amplification of enhanced backscattering from a dye-doped polymer bounded by a rough surface

Abstract: We report the experimental study of the enhanced backscattering from a random rough surface through a laser dye-doped polymer. The sample is a slice of pyrromethene-doped polymer coupled with a two-dimensional rough gold layer with a large slope. When the sample is illuminated with an s-polarized He-Ne laser and pumped by a cw argon-ion laser, amplified backscattering is observed. The enhanced backscattering peak increases sharply and its width narrows for a sample with low dielectric constant |?(2)|.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…Or, in other words, the enhanced backscattering peak becomes narrower and taller when the amplification of the medium is increased. This behavior is in qualitative agreement with the experimental results reported recently by Gu and Peng [6]. This finding can theoretically be understood as follows: It can be shown that the enhanced backscattering peak should have a Lorentzian form of total width [5] ∆ T (ω) = ∆ ǫ (ω) + ∆ sc (ω), (3.1) where ∆ ǫ (ω) is the contribution to the width from the attenuation or amplification of the guided waves, while ∆ sc (ω) is the broadening due to the scattering of such waves by the surface roughness.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Or, in other words, the enhanced backscattering peak becomes narrower and taller when the amplification of the medium is increased. This behavior is in qualitative agreement with the experimental results reported recently by Gu and Peng [6]. This finding can theoretically be understood as follows: It can be shown that the enhanced backscattering peak should have a Lorentzian form of total width [5] ∆ T (ω) = ∆ ǫ (ω) + ∆ sc (ω), (3.1) where ∆ ǫ (ω) is the contribution to the width from the attenuation or amplification of the guided waves, while ∆ sc (ω) is the broadening due to the scattering of such waves by the surface roughness.…”
Section: Resultssupporting
confidence: 93%
“…Only recently has the surface scattering community begun on studies of surface disordered amplifying systems. The only literature on the scattering of light from amplifying surface disordered media known to us is the theoretical study by Tutov et al [5] and the experimental investigation by Gu and Peng [6]. In the theoretical work by Tutov et al [5] the authors conducted a perturbative study of the scattering of s-polarized light from an amplifying film deposited on the planar surface of a perfect conductor, where the vacuum-film interface was a one-dimensional random interface characterized by a Gaussian power spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…[23][24][25][26] It must be mentioned here that at room FIG. [23][24][25][26] It must be mentioned here that at room FIG.…”
Section: Resultsmentioning
confidence: 99%
“…AgI nanoparticles were grown on the surface at the early stage of iodization ͑15 30 min͒, whereas the bottom of the film remains as silver nanoparticles-the two constituting a Ag-AgI composite film. 37,38 The redshift is attributed to the spill out of the s electrons in free electron metals 39 and an increase in the effective mass of the conduction electrons. 5 nm Ag film shows a weak PR1 at 562 nm but after 15 min iodization, a very strong, inhomogeneously broadened plasmon resonance appears at 450 nm, redshifted by a whopping 112 nm possibly due to the effect of the formation of AgI nanoparticles on the surface.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to commercial advantages, these lasers have technical advantages over liquid dye lasers. Several types of materials have been used as host matrices for dye encapsulation [1][2][3][4][5][6][7][8]. Recently, researchers have shown intense interest in the use of low temperature sol-gel technique to prepare solid-state laser materials [4][5][6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%